The global evolution of travel visa regimes: an analysis based on the DEMIG VISA database - Czaika, M; de Haas, H; Villares-Varela, M (International Migration Institute, 2017)
Drawing on the new DEMIG VISA database which covers global bilateral travel restrictions from 1973 to 2013, this paper explores patterns and trends in international visa regimes. We construct indices of cross-regional inbound and outbound travel restrictiveness to investigate (i) the extent to which different world regions and regional unions have opened or closed to other regions and (ii) the ways in which the formation of regional unions or the disintegration of countries or unions of countries (e.g. the USSR) has affected international visa regimes. Generally, the analysis challenge the idea of a growing global mobility divide between 'North’ and 'South’, and yields a more complex image reflecting the rather multi-polar and multi-layered nature of international relations. While the strongest change has been the decreasing use of exit restrictions, the level of entry visa restrictiveness has remained remarkably stable at high levels, with currently around 73 per cent of country dyads being visa-restricted. While predominantly European and North American OECD countries maintain high levels of entry visa restrictiveness for Africa and Asia, these latter regions have the highest levels of entry restrictions themselves. Although citizens of wealthy countries generally enjoy greatest visa-free travel opportunities, this primarily reflects their freedom to travel to other OECD countries. Visa-free travel is mostly realised between geographically proximate countries of integrated regional blocs such as ECOWAS, the EU, GCC and MERCOSUR. Analyses of global dynamics in visa reciprocity show that 21 per cent of the country dyads have asymmetrical visa rules, but also show that levels of reciprocity have increased since the mid-1990s. Our analysis shows that visas are not 'just’ instruments regulating entry of visitors and exit of citizens, but are manifestations of broader political economic trends and inequalities in international power relations.